2009
DOI: 10.1128/iai.01071-08
|View full text |Cite
|
Sign up to set email alerts
|

Factor H-Binding Protein Is Important for Meningococcal Survival in Human Whole Blood and Serum and in the Presence of the Antimicrobial Peptide LL-37

Abstract: Factor H-binding protein (fHBP; GNA1870) is one of the antigens of the recombinant vaccine against serogroup B Neisseria meningitidis, which has been developed using reverse vaccinology and is the basis of a meningococcal B vaccine entering phase III clinical trials. Binding of factor H (fH), an inhibitor of the complement alternative pathway, to fHBP enables N. meningitidis to evade killing by the innate immune system. All fHBP null mutant strains analyzed were sensitive to killing in ex vivo human whole bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 42 publications
4
79
2
Order By: Relevance
“…In this work, the total neisserial transcriptome was analyzed in a time course experiment of incubation in an ex vivo model of bacteremia, using a tiling array. The ex vivo human whole-blood model has shown potential to examine a number of parameters that are likely to be important in the cascade of events associated with acute systemic meningococcal infection (26) and to characterize N. meningitidis factors involved in the survival of the bacterium during infection (13,52).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the total neisserial transcriptome was analyzed in a time course experiment of incubation in an ex vivo model of bacteremia, using a tiling array. The ex vivo human whole-blood model has shown potential to examine a number of parameters that are likely to be important in the cascade of events associated with acute systemic meningococcal infection (26) and to characterize N. meningitidis factors involved in the survival of the bacterium during infection (13,52).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-fHbp antibodies were found in convalescent sera from subjects that contracted meningococcal disease, supporting the expression of fHbps on meningococcal bacteria and their in vivo immunogenicity (8). fHbp is also an important virulence factor expressed by N. meningitidis to evade innate immune defenses by specifically binding to complement factor H (fH) (9). It was suggested that anti-fHbp antibodies can elicit protection by two mechanisms: direct complement-mediated killing of the bacterium and blocking fH binding to the bacteria to increase the susceptibility of the bacterium to killing by the alternative complement pathway (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…fHbp is a 28 kDa surface-exposed lipoprotein and an important component of two meningococcal vaccines currently in clinical development (6)(7)(8)(9). fHbp plays a prominent role in meningococcal pathogenesis by recruiting human factor H (hfH) to the bacterial surface, thus protecting the bacterium from complement-mediated killing (10)(11)(12). fHbp is expressed by the majority of virulent meningococcal strains; its sequence displays extensive variability, allowing classification into three main variant groups (var1, -2, and -3) or two subfamilies (A and B) sharing limited cross-protection (13).…”
mentioning
confidence: 99%